EU Taxonomy and Sustainable Finance : Key Levers for Climate Change Mitigation - Sundqvist, Sara (My University, 2022)
Sustainable finance is mainstreaming. Sustainable finance refers to long-term investments in sustainable economic activities taking environmental, social and governance (ESG) considerations into account. Sustainable finance is a very timely and important issue for achieving the goals of the Paris Climate Agreement and sustainable development. Current levels of investment are insufficient to support an environmentally and socially sustainable economic system. Financial markets cash flows are today too often contributing to environmental destruction, over-consumption and climate change, instead of sustainable technologies and businesses, that would result in sustainable long-term growth. During the last years the European Union (EU) has taken a position as the world leader in promoting sustainable finance. In March 2018 European Commission published its extensive and ambitious Action Plan on Financing Sustainable Growth followed by various new sustainable finance regulations. The most important new sustainable finance regulation is the EU Taxonomy regulation. The EU Taxonomy Regulation (EU 2020/852) aims to enable and increase sustainable investment. It is an EU-wide classification system that provides businesses and investors with a common definition on environmentally sustainable economic activities. The objective of this research is to understand what is sustainable finance and the new EU Taxonomy Regulation. The main research question is: What is the EU Taxonomy and does it, as a classification system for sustainable finance, help in climate change mitigation. The used methodology is regulatory research, since this research focuses on examining a new regulation. The used method is traditional literature review. This research is based on European Commission material and publications, as well as extensive literature, from which research of Schoenmaker and Ehlers et al. can be pointed out as most important. This research concludes that with EU Taxonomy investor preferences are expected to increasingly favour sustainable activities and allocate capital accordingly. EU Taxonomy is expected to help in climate change mitigation.
Keywords: ESG, EU Action Plan, EU Taxonomy, responsible investment, sustainable finance